Improvement of write error rate in voltage-driven magnetization switching. (15th February 2019) - Yamamoto, Tatsuya; Nozaki, Takayuki; Imamura, Hiroshi; Shiota, Yoichi; Tamaru, Shingo; Yakushiji, Kay; Kubota, Hitoshi; Fukushima, Akio; Suzuki, Yoshishige; Yuasa, Shinji
Abstract: We investigate magnetization switching driven by the voltage-controlled magnetic anisotropy (VCMA) effect in two series of magnetic tunnel junctions with a Ta/CoFeB/MgO structure. We demonstrate that improved thermal stability as well as the VCMA effect make it possible to achieve write error rates lower than 10 −6 . We also show that the thermal stability of the free layer plays an important role in suppressing increased write errors due to precession-orbit transition induced by thermal fluctuation.